Production of flour confectionery products with seaweed as a baa - N. V. Sokol; E. A. Shepelenko (Новые технологии, 2017)
In the course of the experiment, natural biologically active substances were selected to enrich the buttery biscuits. Optimum dosages of additives - oatmeal flour and sugary laminaria powder, providing a physiological effect are determined. The paper presents the results of the investigation of the influence of laminaria powder on the structural and mechanical properties of the dough, as well as the quality characteristics of finished products.